Financial Literacy on Investment Decisions: A Reference to Undergraduate Students in Butwal - Riya Timalsina (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2021)
The presence of information and abilities that enable informed and efficient money management is known as financial literacy. The country's financial improvements and economic expansion are being aided by financial literacy. In light of these changes, it's critical to evaluate if the younger generation, particularly students who are viewed as the future investors, movers, and transformers of the economy, has the requisite understanding of financial principles. This study examines the impact of financial literacy on investing decisions among undergraduate in the Butwal area. A total of 500 students from different universities of Butwal areas are participated in this study. The current study used a few characteristics to evaluate students' financial literacy, such as their knowledge of financial products, their ability to access financial goods, their knowledge of money management, their understanding of financial investment options, and their financial abilities. The goal of the study was to determine how a student's level of financial literacy affects his or her financial beliefs, choices, and behaviors. The results showed that undergraduates investing decisions were favorably and significantly impacted by knowledge with financial product. Financial abilities were the most important component when it came to the many aspects of financial literacy. The researcher concludes by offering some recommendations for financial institutions and decision-makers in order to raise financial literacy levels and improve investment performance.